Constraining Morphologies of Soft Tissues in Extinct Vertebrates Using Multibody Dynamic Simulations: A Case Study on Articular Cartilage of the Sauropod Dreadnoughtus - Voegele, Kristyn K.; Bonnan, Matthew F.; Siegler, Sorin; Langel, Christopher R.; Lacovara, Kenneth J. (Frontiers in Earth Science, 2022)
Rarity of soft tissue preservation, including of articular cartilage, in the fossil record hinders creation of biologically-realistic mechanical models. Previous studies of articular cartilage in extant taxa have documented important aspects of cartilage shapes and thicknesses, but these insights remain generalized and have yet to see systematic implementation in biomechanical modeling. Herein, we present a new method for modeling joints that allows for testing of hypotheses about articular cartilage morphology in extinct taxa. Our case study examines the left elbow joint of the sauropod dinosaur Dreadnoughtus schrani using articular cartilage reconstructions constrained by extant phylogenetic bracketing (EPB). EPB investigations of alligator and chicken articular cartilage revealed the presence of a spherical anterior projection of cartilage on the distal humerus which articulates with the radius during flexion. Importantly, this shape does not directly mirror the underlying bone. Using multibody dynamic models created in Adams™ without a priori restrictions on joint degrees of freedom, we simulated the effects of three alternative cartilage reconstructions based on these EPB findings which differ in mediolateral placement of a cartilage sphere and its anteroposterior thickness, encompassing a range of possibilities for the condition in Dreadnoughtus. Bone kinematics and contact area (calculated in Geomagic®) were tracked. Additionally, we modeled the elbow of an alligator and turkey using the same methodology and compared the results to XROMM (X-ray Reconstruction of Moving Morphology) analysis of the same limbs. Each model produced distinct results but were generally similar supporting our modeling methodology. Based on these findings, we predict that Dreadnoughtus, and presumably other extinct archosaurs, had a spherical projection of cartilage on the anterior face of the distal end of the humerus for articulation with the radius. Though many valuable insights have been gained by existing modeling methodologies, we chose a different approach that focused on joint contact surfaces. . Moreover, applying our methods within a quantitative hypothesis-testing framework can advance the field of paleobiology by testing hypotheses relating shape and kinematics that are not possible with prescribed joint motions.